The Global Middle Class: A New Conceptual and Measurement Framework for the Developing Countries. - Lama, Gyanesh; Sened, Itai (Social Development Issues (Follmer Group), 2018)
The role of the middle class in the evolution of societies, their economies, and their politics is one of the oldest topics in political economy. Yet the middle class remains a little understood and understudied social class. The myopic view that middle income is synonymous with middle class has led to misleading conclusions about the nature and size of the middle class and its contribution to the social development of a society. To our knowledge, there is no standardized conceptual and measurement framework for the study of the middle class. Building on Aristotle's original concept of the middle class, we will present a new conceptual and measurement framework that is based on a strong theoretical foundation and empirical base. We have used empirical tests to evaluate the use of our conceptual and measurement frameworks in select developing countries for which data were available. The article will present preliminary findings from these experiments and consider future directions for research.